Cybernorms: Analysis of International Norms in France's Paris Call for Trust and Security in Cyberspace - Diko Catur Novanto; Ika Riswanti Putranti; Andi Akhmad Basith Dir (Journal of Islamic World and Politics, 2021)
Cybercrime is a crime involving computers and networks that began to develop after the Cold War. International politics also have developed through computer networks or cyberspace, especially in communication and diplomacy. Many actors who have different interests make the cybersphere unstable. Several state and non-state actors themselves have collaborated and conventions in the cyber realm. In 2018, France made a high-level declaration called the Paris Call for Trust and Security in Cyberspace to maintain stability in cyberspace. Through the Paris Call, France tries to establish an international norm in the cyber domain known as Cybernorms. This norm has been supported by several state and non-state actors. This study seeks to see the importance of the Paris Call that has been made by the French government which aims to remind the general norms of cyber that are not popular or see the formation of international norms in the cybersphere. This study uses a qualitative method with the process-tracing data analysis method used to explain change and cause-and-effect. This research argues that cyber norms are very important for state or non-state actors in maintaining the stability of the cyber world.